Children of Alcatraz : growing up on the rock - Murphy, Claire Rudolf (Walker & Co., 2006)
Alcatraz Island is one of the most infamous places in American history. The maximum-security prison on the "Rock," once home to criminals like Al Capone, Machine Gun Kelly, and the Birdman of Alcatraz, has long since captured our country's imagination. But what few people realize is that during the past 200 years, Alcatraz was not only home to criminals<U+2015>it was home to many children, too! Over the years, the island has been home to the children of Native Americans, lighthouse keepers, military soldiers, and prison guards. Imagine playing hide-and-seek in the prison morgue, having a convict as your babysitter, or having Al Capone as your neighbor. This compelling photo-essay profiles generations of children who had the unique opportunity of growing up on this isolated island in San Francisco's shadow. With personal anecdotes, revealing interviews with the surviving Alcatraz Kids, historical documents, and archival and family photographs, Children of Alcatraz reveals a one-of-a-kind childhood sure to fascinate readers young and old.